What the analysis of extended meaning of terms can reveal about verb semantic frame structure. Issue 1 (2nd January 2020) - Ureña Gómez-Moreno, José Manuel; Faber, Pamela
ABSTRACT: By disabling two traditional constraints on general-language one-verb sub-events, Goldberg shows that: (i) a verb can specify both manner and result or change of location; and (ii) the profiled event of one verb need not be causally related to the evoked background frame event. This study develops Goldberg's claims further to show that a single verb can meet (i) and (ii) at the same time. For this purpose, two polysemic terminological verbs and their arguments were analyzed as they occur in concordances extracted from a corpus of naturally running texts from the specialized knowledge domain of environmental science. The meanings of these verbs and of their arguments were formalized in the Environmental Event Frame as described by Faber et al. The basic senses of the verbs in ordinary language were compared with their extended terminological meanings to determine how meaning extension structures and constrains the event-based semantic frame evoked by each of the sub-senses of the verbs. Striking differences were found in the nature and composition of the semantic frames of the pairs of senses compared. This type of semantic frame asymmetry in polysemic verbs that satisfy criteria (i) and (ii) further enriches Goldberg's theory of verb semantics and event-structure construal.